Female board representation and provisioning practices in Nigerian banks (Journal of Economic Research & Business Administration, 2020)
The removal of board members of deposit money banks (DMBs) in Nigeria with larger proportion ofmale directors in the last decade (2009-2018) for corporate reporting and governance irregularities hasbecome commonplace. Also, the indifference of the extant corporate governance code in the Nigerianbanking industry to the gender diversity in the DMBs’ boards despite the global phenomenal natureof the practice poses a lot of questions. Given these rationales, this study examined the influence offemale board representation on the practices of income smoothing via provision for loan losses. Thetime-series cross-sectional dataset related to the variables of the study for a sample of 15 DMBs wereextracted from the annual reports of these banks for the period 2007-2018. Data collected were analysedusing Prais-Winsten regression model with correlated Panel-Corrected Standard Errors (P-W/PCSEs).The results showed, on the whole, that the reduction in income-smoothing practices is engendered bythe extent of female board representation given the significantly negative coefficients of proportion offemale directors and Blau Diversity Index. Specifically, among the five continuous measures of femalerepresentation, proportion of female directors and Blau Diversity Index explain better the reduction inthe income-smoothing practices. For five categorical female representation indicators, presence of atleast one woman in the audit committee (F1AD), presence of at least three women on the board andhaving female chief financial officer (FCFO) are better predictors but that of F1AD is contrary to the priorexpectations. The study also established that the reduction in earnings-smoothing practices cannot takeplace until a critical mass of female board members is present. The study solicited for the appointment ofat least three female directors and having female CFO on the DMBs’ boards among others.